الرَّبطُ وأثرُه الدِّلالي في شعرِ أبي إسحاق الإلبيريّ دراسة لغوية - النمراوي إيمان محمد خلف مرهاش; معوض سليمان شهيد (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Linguistic linking is of great importance in the Arabic language, as it works to cohese linguistic texts, whether poetic or prose, and to cast them and protect them from slipping. It is credited with forming relationships between the elements of the text, which makes ideas clear and meanings prominent and understandable to the recipient. The subject of linking is evident in Abu Ishaq al-Ilbiri’s poetry in several aspects and various tools, in which the poet worked hard to highlight the meanings and ideas that revolve in his mind and make them accessible to the recipients’ understanding. The poet used various tools of linguistic links represented by conjunctions, pronouns, demonstrative pronouns, and other tools, which achieve textual cohesion and enhance the understanding of meanings and the recipient’s interaction with the text. Linguistic linking has a great impact on understanding texts by creating clear relationships between sentences and phrases and enhancing them to understand the general context of the texts and understand the intended meanings and new connotations.